The role of circulating lipid chaperone proteins in insulin signalling and inflammation - Mohd Radzuan, Hazulin; Bennett, Andrew J.; Cole, Mark A. (2017)
A growing body of evidence indicates that adipose tissue actively secretes lipid chaperone proteins into circulatory system, such as fatty acid binding protein4 (FABP4) and lipocalin2 (LCN2). FABP4 have been implicated in the pathogenesis of obesity-induced insulin resistance, whereas role of LCN2 is less clear; being described as causing insulin resistance or sensitization in different model systems. We have examined the effects of varying glucose concentrations in normoxic and hypoxic conditions which mimic normal and obese/diabetic condition. Primary rat adipocyte culture was carried out using visceral adipose tissues from Wistar rats. They were maintained in 2 different glucose concentrations media (6mM and 17.5mM). They were also given hypoxic treatment via hypoxic chamber (2% O2, 5% CO2 and 93% N2) or normoxic incubator (21% O2) for 24 hours. The effect of hyperglycaemia and hypoxia upon FABP4 and LCN2 mRNA expression done by using Taqman q-PCR. The protein secretion from cells treated with different glucose concentration media at different stages of adipogenesis was detected by immunoblotting. The results showed that hypoxia had no significant effect upon either FABP4 or LCN2 mRNA levels. Increasing glucose concentration from 6mM to 17.5mM caused increased FABP4 expression and decreased expression of LCN2. Meanwhile, LCN2 is secreted at high levels during early stages of adipogenesis, whereas FABP4 secretion was only detected from mature adipocytes. Therefore, different glucose concentration and adipocytes differentiation state affects these lipid chaperone proteins regulation, which may play a role as paracrine signalling in normal or metabolic diseases.